Lactate production as representative of the fermentation potential of Corynebacterium glutamicum 2262 in a one-step process. Issue 2 (1st February 2014) - Khuat, Hoang Bao Truc; Kaboré, Abdoul Karim; Olmos, Eric; Fick, Michel; Boudrant, Joseph; Goergen, Jean-Louis; Delaunay, Stéphane; Guedon, Emmanuel
Abstract: The fermentative properties of thermo-sensitive strain Corynebacterium glutamicum 2262 were investigated in processes coupling aerobic cell growth and the anaerobic fermentation phase. In particular, the influence of two modes of fermentation on the production of lactate, the fermentation product model, was studied. In both processes, lactate was produced in significant amount, 27 g/L in batch culture, and up to 55.8 g/L in fed-batch culture, but the specific production rate in the fed-batch culture was four times lower than that in the batch culture. Compared to other investigated fermentation processes, our strategy resulted in the highest yield of lactic acid from biomass. Lactate production by C. glutamicum 2262 thus revealed the capability of the strain to produce various fermentation products from pyruvate.